Pengaruh Pengetahuan Sumber Daya Manusia, Implementasi Sistem Keuangan Desa (Siskeudes) dan Sistem Pengendalian Internal terhadap Kualitas Penyajian Laporan Keuangan Desa: (Studi Kasus pada Pemerintah Desa di Kasbupaten Sukoharjo) - Bunga Nisa Isnaini; Era Trianita Saputra (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2024)
This study was conducted with the aim of knowing the extent to which the quality of village financial reports can be influenced by human resource (HR) knowledge, SISKEUDES implementation and internal control systems. This study uses a quantitative method with primary data collection, namely a questionnaire. The population in this study was 160. The sampling techniques used purposive sampling, so that 100 people were used. The data analysis techniques used were data instrument testing, classical assumption testing, multiple regression analysis and hypothesis testing. Based on the results of the study, human resource (HR) knowledge, SISKEUDES implementation and internal control systems partially influenced the quality of village financial reports.